New data of chrysophycean stomatocysts from Lake Baikal - A. D. Firsova; A. Yu. Bessudova; Ye. V. Likhoshway (Acta Biologica Sibirica, 2017)
The chrysophyte stomatocyst composition in phytoplankton of Lake Baikal in 2016 was studied using scanning electron microscopy. 20 morphotypes were detected, 8 of which were seen in the lake for the first time, and 5 were described as novel. For 3 morphotypes the species was determined based on the scale presence and structure.